The infrared peak of the blazar spectral energy distribution and the monitoring from Antarctica - S. Ciprini; BUSSO, Maurizio Maria; TOSTI, Gino (2003)
Blazars are a class of Active Galactic Nuclei (AGN) with a highly luminous and rapidly variable non-thermal emission. Their overall Spectral Energy Distribution (SED) is a smooth and featureless continuum with a typical two bump structure due to synchrotron and inverse Compton radiation. The energy budget of blazar is dominated by infrared emission from 1 mu m to 100 mu m. The low frequency peaked blazar (LBL) and intermediate blazar, typically emit from 1/3 to 2/3 of the total luminosity in this range. We report some simulations of the SED of two intermediate objects, ON 231 and BL Lac. Using the available multiwavelength data, during some phases of variability a relevant peak of mid infrared emission was predicted, but there was always a large gap of observation between the radio and near-IR/optical bands, for any blazar, to really constraint the model. We remark that a moderate-size telescope like IRAIT, placed in the Antarctica plateau, might give just a unique way to perform a mid-IR monitoring of the southern blazars variability, also as a secondary program. This could be crucial to constraint the global energetics and models, and might allow to obtain decisive mid-IR fluxes during the multiwavelength observing campaigns.